1991
DOI: 10.1038/ki.1991.257
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial cell behavior in a three-dimensional extracellular matrix

Abstract: To understand the role of mesangial matrix in regulating responses of mesangial cells (MCs), particularly as a cause of disease, we examined the behavior of MCs cultured in a three-dimensional extracellular matrix (ECM). Mouse and rat MCs were incorporated into ECM composed of type I collagen gel matrix (CGM) and basement membrane-type gel matrix (BGM), and their shape and proliferation were assessed. The effect of gel matrix on MC migration was also studied. MCs exhibited marked elongation and proliferation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Rat mesangial cells were established from isolated renal glomeruli of an adult male Sprague-Dawley rat (7). A cell clone SM43 was established by a limiting dilutional method and identified as being of mesangial cell phenotype as described (25). By using a modified calcium phosphate coprecipitation method (26), SM43 mesangial cells were cotransfected with a regulator plasmid pUHD15-1 encoding tTA (21) and a plasmid pRc/CMV (Invitrogen) that introduces a neomycin phosphotransferase gene.…”
Section: Methodsmentioning
confidence: 99%
“…Rat mesangial cells were established from isolated renal glomeruli of an adult male Sprague-Dawley rat (7). A cell clone SM43 was established by a limiting dilutional method and identified as being of mesangial cell phenotype as described (25). By using a modified calcium phosphate coprecipitation method (26), SM43 mesangial cells were cotransfected with a regulator plasmid pUHD15-1 encoding tTA (21) and a plasmid pRc/CMV (Invitrogen) that introduces a neomycin phosphotransferase gene.…”
Section: Methodsmentioning
confidence: 99%
“…Rat mesangial cells were established from isolated renal glomeruli of an adult male Sprague-Dawley rat (27). A cell clone SM43 was established by a limiting dilution method (1) and identified as being of mesangial cell phenotype as described (27). Using a modified calcium phosphate coprecipitation method (28), SM43 mesangial cells were transfected with an expression plasmid pSRE-lacZ (29).…”
Section: Methodsmentioning
confidence: 99%
“…Rat mesangial cells were established from isolated renal glomeruli of an adult male Sprague-Dawley rat (27). A cell clone SM43 was established by a limiting dilution method (1) and identified as being of mesangial cell phenotype as described (27).…”
Section: Methodsmentioning
confidence: 99%
“…In the particular case of mesangial cells, different phenotypic changes have been described when cells were grown under these conditions [10, 11, 12, 13]. For instance, Saito et al [11]demonstrated that the mesangial cell proliferation is different when collagen type I or collagen type III, both are often observed in diseased glomeruli, is present.…”
Section: Introductionmentioning
confidence: 99%